Impact of blood pressure lowering on cardiovascular outcomes in normal weight, overweight, and obese individuals: The perindopril protection against recurrent stroke study trial - Czernichow, S.; Ninomiya, T.; Huxley, Rachel; Kengne, A.; Batty, G.; Grobbee, D.; Woodward, M.; Neal, B.; Chalmers, J. (American Heart Association, 2010)
There is considerable uncertainty regarding the efficacy of blood pressure-lowering therapy in reducing cardiovascular risk in obese people. In this report we examine the effects of blood pressure lowering according to baseline body mass index (kilograms per meter squared) in the Perindopril Protection Against Recurrent Stroke Study. A total of 6105 participants with cerebrovascular disease were randomized to perindopril-based blood pressure-lowering therapy or placebo. The overall mean difference in systolic/diastolic blood pressure between participants assigned active therapy or placebo was 9/4 mm Hg (SE: 0.5/0.3 mm Hg), with no difference by body mass index quarters (<23.1, 23.1 to 25.3, 25.4 to 27.8, and =27.9 kg/m). A consistent treatment benefit was demonstrated for protection against major vascular events across quarters with the following hazard ratios (95% CIs): 0.80 (0.62 to 1.02), 0.78 (0.61 to 1.01), 0.67 (0.53 to 0.86), 0.69 (0.54 to 0.88), and 0.74 (0.66 to 0.84; P for heterogeneity=0.16). Similar results were apparent for stroke and stroke subtypes (all P for heterogeneity =0.07) or with the standard definitions of overweight and obesity (<25, 25 to 29, and =30 kg/m; all P for heterogeneity =0.28). The absolute effects of treatment were, however, more than twice that in the highest compared with the lowest body mass index quartile. Across increasing quarters of body mass index over 5 years, active therapy prevented 1 major vascular event among every 28, 23, 13, and 13 patients treated. In conclusion, blood pressure-lowering therapy produced comparable risk reductions in vascular disease across the whole range of body mass indices in participants with a history of stroke. However, the greater baseline level of cardiovascular risk in those with higher body mass index meant that these patients obtained the greatest benefit. Copyright © 2010 American Heart Association. All rights reserved.